The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0222131
|View full text |Cite|
|
Sign up to set email alerts
|

A review of the elusive bicolored iris Snouted Treefrogs (Anura: Hylidae:Scinax uruguayus group)

Abstract: The genus Scinax currently includes more than 120 species, recovered in two major clades, the S. catharinae and the S. ruber clades. The latter comprises 75 species, most of which remain unassigned to any species groups, while 12 are included in the S. rostratus and S. uruguayus groups. In this paper we present a taxonomic review of the two species currently included in the S. uruguayus group, discussing some putative phenotypic synapomorphies of this group. Although S. pinima and S. uruguayus have been consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 89 publications
(152 reference statements)
1
24
0
Order By: Relevance
“…Similarly to other species within this group, the new species also occurs in open formations in ecotone areas with subtropical forests (Giaretta and Sazima 1993;Kwet and Faivovich 2001;Caldart et al 2010). The geographical distribution of P. bigibbosa species group is similar to those reported for the genus Julianus that include a disjunct gap of J. pinima, i.e., a northern relictual distribution associated to rock outcrops of the Espinhaço Mountain Range of Minas Gerais state, and a southern distribution along the highland grasslands of Paraná, Santa Catarina and Rio Grande do Sul states (Baldo et al 2019). In South Brazil, there is open formations along different vegetational ecotones.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly to other species within this group, the new species also occurs in open formations in ecotone areas with subtropical forests (Giaretta and Sazima 1993;Kwet and Faivovich 2001;Caldart et al 2010). The geographical distribution of P. bigibbosa species group is similar to those reported for the genus Julianus that include a disjunct gap of J. pinima, i.e., a northern relictual distribution associated to rock outcrops of the Espinhaço Mountain Range of Minas Gerais state, and a southern distribution along the highland grasslands of Paraná, Santa Catarina and Rio Grande do Sul states (Baldo et al 2019). In South Brazil, there is open formations along different vegetational ecotones.…”
Section: Discussionsupporting
confidence: 73%
“…The hidden surfaces of thighs dark colored with light irregular pale blotches, yellow in living specimens differentiate Scinax x-signatus from S. altae, S. auratus, S. baumgardneri, S. boesemani, S. cretatus, S. crospedospilus, S. cruentomma, S. cuspidatus, S. danae, S. elaeochroa, S. exiguus, S. fuscomarginatus, S. ictericus, S. iquitorum, S. madeirae, S. manriquei, S. pachycrus, S. ruberoculatus, S. staufferi, S. strussmannae, S. squalirostris, S. tsachila, S. villasboasi, S. wandae, and species of the S. uruguayus Group (hidden surfaces of thighs uniform, light or dark colored; e.g., Rivero, 1961;Duellman, 1970Duellman, , 1986Lutz, 1973;De la Riva, 1990;Duellman & Wiens, 1993;Barrio-Amorós et al, 2004;Nunes & Pombal, 2011;Brusquetti et al, 2014;Ferrão et al, 2018a, b;Ron et al, 2018;Baldo et al, 2019; this study), S. funereus, S. onca, and S. iquitorum (hidden surfaces of thighs with horizontal or irregular dark blotches; Duellman, 1971;Ferrão et al, 2017;Moravec et al, 2009; this study), and from species of the S. rostratus Group (hidden surfaces of thighs uniform light or marked with bold dark and light mottling or broad vertical bars; Duellman, 1972aDuellman, , 1973Henle, 1991;Lescure & Marty, 2000;Lima et al, 2005; this study).…”
Section: Comparisons With Other Species Of Scinax Ruber Cladementioning
confidence: 99%
“…Scinax currently includes 125 species in two major clades, the S. catharinae and the S. ruber Clades (species number from Frost, 2020; taxonomy of Scinaxini as recognized by Faivovich et al, 2018). The latter clade includes 75 species; three in the S. uruguayus species Group (Faivovich et al, 2005;Baldo et al, 2019), 10 in the S. rostratus species Group (Lima et al, 2005), and 62 unassigned to any species group. These are mostly the result of a phylogenetic analysis (Faivovich, 2002) that rejected the monophyly of most species groups recognized at that time for the species now included in the S. ruber Clade.…”
Section: Introductionmentioning
confidence: 99%
“…The current number of 32 anuran species of Iguazú National Park and surrounding buffer area is remarkable and represents approximately 52% of the species of anurans from Misiones Province, and 18% of the anurans from Argentina (Vaira et al, 2012;Cardoso & Pereyra, 2018, Baldo et al, 2019. Research in other protected areas of Misiones reported 15 species of anurans 8 km apart from INP (López & Kubisch, 2008), 21 species 110 km apart from INP (López & Nazer, 2009), 20 species 45 km apart from INP (Lescano et al, 2013) and recently Gangenova et al, (2018) reported 18 species in the native forest of the INP and the Urugua-í Provincial Park -adjacent to INP.…”
Section: Discussionmentioning
confidence: 99%